LOCAL CULTURAL LITERACY AND ITS PROMOTION - Muljani, Retno; Sunarto, Emanuel (International Journal of Humanity Studies (IJHS), 2018)
As a place of conservation, research, education, and entertainment, a museum can support formal educational institutions to introduce kinds of literacy, including local cultural literacy. Local  cultural  literacy in this  study referred to  the knowledge of  wayang ( = puppets) belonging  to Museum Wayang Kekayon Yogyakarta (MWK).  Visitors  to MWK can learn the tangible and intangible aspects of  wayang collections  of  MWK. As a preliminary study of a multi-year research, this study addressed two research questions: 1) what educational functions can be promoted through MWK collections? and 2) what criteria should  promotional media  have  in order to promote MWK? The study implemented hermeneutic approach supported by theories of  Semiotics,   Discourse, Pragmatics, and   Web Usability. Data were collected by browsing the Internet, conducting observations while visiting MWK, interviewing experts on museum, wayang, and semiotics and MWK educators. The findings of the study were 1) the identification of  MWK educational functions  to introduce cultural literacy and other relevant philosophical values, and 2) the CLEAR criteria of effective promotional media to promote  cultural (wayang) literacy in the digital era. The study recommended that fun but meaningful activities should be conducted at MWK, and relevant resources and tools should be provided  and used  to support the  activities.DOI: https://doi.org/10.24071/ijhs.2018.020104